The case of a 26_year_old male with subacute progressive visual loss - Thanakit Pongpitakmetha; Pasin Hemachudha; Wanakorn Rattanawong (My University, 2023)
interACTN Case #38: Available: https://interactn.org/2023/11/29/case-38-case-of-a-26-year-old-man-with-subacute-progressive-visual-loss/ A 26-year-old male with HIV was referred from an infectious disease specialist due to an abnormal finding on fundoscopy. For 3 months, the patient has noticed a maculopapular rash on his palms and soles. He has found penile ulcers and has noticed weight loss of over 10 kg over the past 2 months. A month before his hospital visit, he started to have blurry vision and could not view things as clearly as before. He described the landscape as “foggy.” He denies any loss of color vision, headache, or diplopia. He could still maintain his activities of daily living. Two weeks later, his visual symptoms worsened as he experienced more acuity loss along with desaturation of red colors. No pain on eye movement was evident. On fundoscopic examination, he was found to have bilateral 360-degree optic disc edema with profound elevated and blurring margins of both eyes with no hemorrhage or exudate visualized (Fig. 1). Optical coherence tomography (OCT) shows generalized increase retinal nerve fiber layer thickness and retinal rim thickness of both eyes which was beyond the 95th percentile of the standardized Asian population (Fig. 2). Cerebrospinal fluid analysis shows mild pleocytosis and elevated protein. Serum treponema pallidum hemagglutination assay (TPHA) was positive. Therefore, syphilitic optic neuropathy was suspected. The patient was given aqueous penicillin G 18 mU/day intravenously for 14 days followed by intramuscular injection of benzathine penicillin G 2.4 mU weekly for 3 weeks consecutively.1 After the course was completed, antiretroviral therapy was initiated. After 2 months of treatment, his optic disc edema was much improved without new symptoms. Syphilitic optic neuropathy in person with HIV.
Keywords: Optic neuritis; Syphilis Diagnosis and Treatment